Supplying outcomes in the energy technology sector: A multiple case study - Korkeamäki, Lauri (My University, 2018)
The cost-driven competition in industrial manufacturing has pressured the solution sellers to develop solutions creating higher usability and availability. An extremely advanced form of service offerings, called outcome-based or performance-based contracting, has emerged as an alternative to the high-cost expert solutions. Therein, the customer and the provider enter a contract, in which for instance utilization hours are calculated as billable. There, the provider agrees to carry the operational risks of the customer, to justify marginal gains. Probably the best-known example of outcome-based contracting is the Rolls-Royce’s Power by the Hour -contracts, where instead of selling airplane engines, the supplier provides operational hours. The Rolls-Royce model covers the economic risk factor by leasing. The aim of this study is to find out whether other energy technology companies, such as Outotec, ABB and Wärtsilä, already explore the possibilities of outcome-based contracting, with alterations to their value systems. Thus, the theoretical contributions of this study concern the constituent uncertainties leading to interorganizational resistance towards the changes required. Secondly, multiple risk dimensions have been detected to be associated with outcome-base business models. Thirdly, individual response tactics for responding to the organizational resistance towards servitization have been identified. The findings of the study include (I) a framework identifying the sources of interorganizational resistance, indicating strongest connections to strategic and procedural resistance, (II) risk-mitigation practices and (III) individual response tactics for responding interorganizational resistance types. Finally, we conclude that the case companies studied utilize outcome-based contracting through external investors as intermediaries, while remaining the operators themselves.
Keywords: Outcome-based contracting; Outcome-based business models; Performance-based contracting; Performance-based business models; Microfoundations in Servitization; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Master’s Programme in Strategic Business Development|